Jurisdiction Of Drug Distribution On Rural And Urban Users - Dimas Putra Catur P; Yeni Widowaty (Widya Yuridika, 2023)
Drug trafficking in rural and urban areas continues to increase in the number of users. This is based on the results of the Indonesia Drugs Report (IDR) 2022 BNN comparing the number of users between 2019 and 2021, where the results show an increase in the number of users increasing from 1.80% in 2019 to 1.95% in 2021, users also influence the growth from among women who experienced an increase from 0.20% in 2019 to 1.21% in 2021. An interesting question is whether the prevention policies and counseling activities regarding drug use in rural and urban areas have been quite effective, which are still increasing and what preventive measures should be taken by the Indonesian government to reduce the number of drug users. This paper will focus on and examine the policy initiatives and strategies of the Indonesian government, with BNN as a direct extension of the government in overcoming drug abuse and the challenges it faces. By taking theoretical research related to this study, using normative juridical research methods to provide an overview of the object of research and to assist the author in analyzing the correct conclusions. The influence of family, economic and living environment factors causes the government's role ineffective in reducing the number of drug users. Therefore, the government must strengthen interventions starting from the family and community and improvement of rehabilitation facilities.